Industrial Symbiosis in the Circular Economy: A Review - Keçi, Ina (ECONOMICUS, 2024)
Purpose: This article provides an overview of industrial symbiosis in the context of a regenerative economy. As industrial symbiosis represents a novelty in sustainable development, this area has yet to be explored in depth. Despite the research interest in the circular economy, only some studies have considered the philosophy of industrial symbiosis. The primary purpose of this study is to analyse the current body of research to establish a framework that clarifies the connection between the ecological economy and industrial symbiosis and the variables that enable it. Design/methodology/approach- A literature review examines and evaluates the knowledge background. A semi-systematic analysis was issued by employing an assessment synthesis approach. A thorough investigation and analysis of related and current published works was conducted by carefully choosing articles from diverse scholarly databases. Findings- The interaction between the environment and industry is crucial for industrial enterprises’ functioning, as the climate’s consequences exert a constant and growing struggle against them. Implementing industrial symbiosis would encourage the cooperation and integration of socioeconomic and ecological systems in our society by developing a circular economy, which would also be a significant and forwardthinking step towards achieving eco-industrial development. Originality/value- This investigation contributes to understanding how business organisations can support sustainable development and deal with environmental issues by implementing the industrial symbiosis agenda. Substantial contribution is offered to the subject of sustainable development by providing strategic insights into the future agenda for business organisations.